Eficiência agronômica de fontes de manganês, disponibilidade para a soja e distribuição nas frações do solo - São João, Andréia de Cássia Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
A greenhouse experiment was carried out to evaluate the effects in soil, plant and soybean dry matter yield in function of manganese rates and sources. The distribution of manganese in different fractions was evaluated. A completely randomized design in a factorial arrangement 3x6x3 (soil x rate x Mn source) was used. The soils were classified as Typic Quartzipsamment (soil 1), clayey Typic Haplustox (soil 2) and sandy clay loam Typic Haplustox (soil 3). Mn rates were 0, 5, 10, 20, 40 e 60 mg kg-1 using single superphosphate + Mn (micronutrient incorporated in ordinary superphosphate granulation), Fritted Mn and manganese sulphate. The available Mn was determined with Mehlich-1 (M-1) and DTPA. The extractants used to evaluate Mn solubility in fertilizers were: water, 20 g L-1 citric acid and neutral ammonium citrate solutions. The agronomic effectiveness of the manganese sources was calculated using manganese sulphate as reference. Using sequential extraction, the soil Mn was partitioned into exchangeable, organic, amorphous Fe and Al oxides, crystalline Fe and Al oxides and residual forms. Mn fertilization increased Mn content in soybean shoot, regardless to soil and source considered. Dry matter yield depended of Mn initial in soils. In soils 1 and 2, which had low Mn content, occured an increase in soybean dry matter yield. The DTPA and M-1 extractants were efficient to evaluate the Mn availability to soybean. The fritted Mn source resulted lower agronomic effectiveness in comparison to SS+Mn and MnSO4...(Complete abstract, acess undermentioned eletronic adress)
Keywords: Sequential extraction; Manganês; Soja; Elementos traços na nutrição; Extração seqüencial